2014
DOI: 10.1038/srep07070
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy for the treatment of malignant infarction of the middle cerebral artery

Abstract: Early decompressive craniectomy (DC) has been shown to reduce mortality in malignant middle cerebral artery (MCA) infarction, whereas efficacy of DC on functional outcome is inconclusive. Here, we performed a meta-analysis to estimate the effects of DC on malignant MCA infarction and investigated whether age of patients and timing of surgery influenced the efficacy. We systematically searched PubMed, Medline, Embase, Cochrane library, Web of Science update to June 2014. Finally, A total of 14 studies involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
3
23
0
6
Order By: Relevance
“…Individuals affected by a malignant ischemic event are seldom discharged without severe clinical deficits; this data is in accordance with a recent study of meta-analysis carried out in China, involving more than 700 patients, that considered an mRS of 4 a good functional result 10 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Individuals affected by a malignant ischemic event are seldom discharged without severe clinical deficits; this data is in accordance with a recent study of meta-analysis carried out in China, involving more than 700 patients, that considered an mRS of 4 a good functional result 10 .…”
Section: Discussionsupporting
confidence: 89%
“…In order to clearly define the indication for the surgical treatment and to decrease complications derived from DC in a university hospital in southern Brazil, a specific protocol for DC in the treatment of intracranial hypertension derived from ischemia of the MCA region has been implemented since 2007, in conjunction with the neurology department. Even though studies have demonstrated the efficacy of DC in patients presenting with malignant MCA infarction 5,6,7,8,9,10 , some resistance to its application still exists, particularly regarding the functionality of the patients who survive the acute event.The goals of the present study were to assess the mortality rates from the use of DC in the treatment of patients …”
mentioning
confidence: 99%
“…It was shown repeatedly that early DHC performed within 24 h after onset of symptoms significantly reduced mortality and improved outcome 6 and 12 months after stroke [44,45] . DHC performed 48 h after stroke onset might not have a beneficial effect on mortality or clinical outcome [51] . Additionally, the size of the hemicraniectomy is important and a diameter of DHC of at least 12 cm is recommended in most studies.…”
Section: Dhcmentioning
confidence: 96%
“…48 Although this finding may be a result of selection bias, this effect may be similar to that in patients with large hemispheric ischemic strokes with malignant edema, such that neurosurgical treatment may reduce mortality by preventing herniation but still leave the patient with substantially disabling neurological deficits. 129 Furthermore, although isolated subdural hemorrhage is a very rare manifestation of sICH, certain patients with isolated subdural hemorrhage may possibly benefit from neurosurgical evacuation. When neurosurgical treatments are considered, they should be performed after coagulopathy reversal, and decisions should be balanced against the risk of hemorrhagic complications in the setting of alteplaserelated coagulopathy.…”
Section: Neurosurgical Treatmentmentioning
confidence: 99%